Hubungan Kadar Glukosa Darah dengan Ulkus Diabetikum - Trijati Puspita Lestari; Arengga Rona Firdiansyah; Isni Lailatul Maghfiroh (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2026)
Diabetic ulcers are one of the serious chronic complications in patients with diabetes mellitus and can cause infection, amputation, and even death if not treated properly. This condition is influenced by various factors, such as uncontrolled blood glucose levels, decreased foot sensitivity due to neuropathy, and poor foot care behavior. This study aims to analyze the relationship between blood glucose levels and the risk of diabetic ulcers. This study used a correlational design with a cross-sectional approach with a sample of 81 patients with diabetes mellitus. Data were collected by examining random blood glucose levels using a glucometer and the risk of diabetic ulcers using an observation sheet. The data were then analyzed using the Spearman's rho test. The results showed that there was a significant relationship between blood glucose levels and the risk of diabetic ulcers, with a significance value of p = 0.000 (p <0.05). Controlling blood glucose levels, early detection of decreased foot sensitivity, and good foot care behavior have an important role in reducing the risk of diabetic ulcers in patients with diabetes mellitus